Normal and anomaly development of embryonic heart outflow tract and outflow tract defects. Participation of neural crest cells - Shapoval K.I. (Морфологія, 2008)
This work analyzes the basic stages of development of the important transient structure in the cardiogenesis - outflow tract (OT). It is the predecessor of aorta and pulmonary trunk, which determines and controls many events of embryonic hearts development: the closure of secundary interventricular foramen, valves formation, aortic vestibule and pulmonary infundibulum development. The basic stages of normal OT development are reorganization of the aortopulmonary septation complex, rotation, formation of conotrunk transition, aortic vestibule and pulmonary infundibulum formation, the closure of interventricular foramen. The abnormalities of these processes cause the birth heart defects. The late closure interventricular septum results in abnormal establishment of aorta and alignment of ventricles with large vessels. The disputable questions concerning terminology, spatial representation and hypothetical models of OT, sources of an origin continue to remain. The future researches will be connected to neural crest cells contribution to OT transformation, namely their influence on processes of cell apoptosis and proliferation.